Unravelling the Taphonomic Stories of Bird Bones from the Middle Pleistocene Layer VIII of Grotte Vaufrey, France - Anna Rufà; Véronique Laroulandie (Quaternary, 2021)
In recent years, several studies have significantly changed our knowledge concerning the use of birds by Neanderthals. However, what remains to be clarified is the geographical and chronological variability of this human behaviour. The present case study provides new information on this topic/debate. The Grotte Vaufrey was discovered during the 1930s and was excavated during different periods. Work carried out by J.-P. Rigaud during the 1980s motivated many multidisciplinary studies in the cave, but accurate studies were not focused on avian remains. In this work, we provide new data on the bird remains from layer VIII (MIS 7), which is the richest among all the sequences and which has an important Mousterian component. Corvids are predominant in the assemblage and are associated with medium-sized birds and small Passeriformes, among others. Most of the remains present modern fractures, which hinder taphonomic interpretation. However, some alterations associated with raptor or mammalian carnivore activities, together with the anatomical representation and age profile, suggest a non-human accumulation of the majority of the bird remains, especially in the case of corvids that naturally died in the cave. However, at least some bones show evidence of anthropic activity, suggesting the occasional use of large- and medium-sized birds by human populations.